Visualising uncertainty: Examining women's views on the role of Magnetic Resonance Imaging (MRI) in late pregnancy. (September 2016) - Reed, Kate; Kochetkova, Inna; Whitby, Elspeth
Abstract: Prenatal screening occupies a prominent role within sociological debates on medical uncertainty. A particular issue concerns the limitations of routine screening which tends to be based on risk prediction. Computer assisted visual technologies such as Magnetic Resonance Imaging (MRI) are now starting to be applied to the prenatal realm to assist in the diagnosis of a range of fetal and maternal disorders (from problems with the fetal brain to the placenta). MRI is often perceived in popular and medical discourse as a technology of certainty and truth. However, little is known about the use of MRI as a tool to confirm or refute the diagnosis of a range of disorders in pregnancy. Drawing on qualitative research with pregnant women attending a fetal medicine clinic in the North of England this paper examines the potential role that MRI can play in mediating pregnancy uncertainty. The paper will argue that MRI can create and manage women's feelings of uncertainty during pregnancy. However, while MRI may not always provide women with unequivocal answers, the detailed information provided by MR images combined with the interpretation and communication skills of the radiologist in many ways enables women to navigate the issue. Our analysis of empirical data therefore highlights the value of this novel technological application for women and their partners. It also seeks to stress the merit of taking a productive approach to the study of diagnostic uncertainty, an approach which recognises the concepts dual nature. Highlights: Explores the emerging use of Fetal MRI in the UK context. Draws on qualitative interviews with pregnant women. Contributes to conceptual debates on diagnostic uncertainty. Communication and interpretation skills of radiologists are highlighted. Health professionals and MR images assist women in their navigation of uncertainty.